Показники набутого та вродженого імунітету у дітей з двостулковим аортальним клапаном серця - Каменщик, Андрій Володимирович; Каменщик, А. В.; Kamenshchyk, A. (My University, 2019)
У 20 дітей з двостулковим аортальним клапаном серця (ДАК) і 30 дітей групи контролю вивчені основні показники придбаного і природженого імунітету і встановлені взаємозв'язку отриманих даних з допплерехокардіографіческімі параметрами. У дітей з ДАК щодо групи контролю встановлено достовірне зниження відносного і абсолютного вмісту CD25 + інтерлейкін-2 рецепторнесущіх активованих лімфоцитів і збільшення відносного і абсолютного вмісту CD95 + субпопуляції лімфоцитів, зниження індексу завершеності фагоцитозу і підвищення показника тесту відновлення нітросинім тетразолия. Виявлено сильні достовірні кореляційні зв'язки зазначених імунологічних показників з допплерерокардіографічними волюметричннми параметрами лівого шлуночка і діаметром аорти. У 20 детей с двустворчатым аортальным клапаном сердца (ДАК) и 30 детей группы контроля изучены основные показатели приобретенного и врожденного иммунитета и установлены взаимосвязи полученных данных с допплерэхокардиографическими параметрами. У детей с ДАК относительно группы контроля установлено достоверное снижение относительного и абсолютного содержания CD25+ интерлейкин-2 рецепторнесущих активированных лимфоцитов и увеличение относительного и абсолютного содержания CD95+ субпопуляции лимфоцитов, снижение индекса завершенности фагоцитоза и повышение показателя теста восстановления нитросинего тетразолия. Выявлены сильные достоверные корреляционные связи отмеченных иммунологических показателей с допплерэхокардиографическими волюметрическими параметрами левого желудочка и диаметром аорты. Introduction: Bicuspid aortic valve (BAV) is the most widespread congenital heart disease with populational prevalence from 1% to 2%. BAV in childhood has mainly asymptomatic course with preserved systolic function despite the high pressure gradient at valve and with severe complications beyond pediatric age. Immune T-cells play an important protective role in formation of valvular fibrosis with regulation of their activity by nuclear factor activating T-cell genes (NFATC) which are also participate in the heart valves embriogenesis. Purpose of the study: to establish the especialities of innate and acquired immunity in children with BAV and revealing the interrelations of obtained values to the basic echodopplerographic parameters in these children. Materials and methods. In 20 children with BAV and in 30 children of control group the basic parameters of acquired and congenital immunity were studied in first level immune investigation. The correlations of obtained immunity data to basic parameters of dopplerechocardiography were established. Result and discussion. In children with BAV compared to control group the significant decrease in relative and absolute values of CD25+ interleukin-2 receptor-bearing activated lymphocytes and the increase in relative and absolute values of CD95+ subpopulation with the decreasing of phagocytosis completeness index and the increase values of nitro blue tetrazolium reduction test were detected. The significant strong correlations of mentioned immunological values to the left ventricle volumetric parameters and to the diameter of aorta in dopplerechocardiography were revealed. Conclusions: In children with BAV the CD25+ and CD95+ cell subpopulations could considered as possible early predictors of aortic valve fibrosis.
Показатели приобретенного и врожденного иммунитета у детей с двустворчатым аортальным клапаном сердца
The values of acquired and congenital immunity in children with bicuspid aortic valve of the heart
Keywords: двостулковий аортальний клапан; діти; CD25 + інтерлейкін-2 рецепторнесущіе активовані лімфоцити; CD95 + субпопуляція лімфоцитів; допплерехокардіографія; двустворчатый аортальный клапан; дети; CD25+ интерлейкин-2 рецепторнесущие активированные лимфоциты; CD95+ субпопуляция лимфоцитов; допплерэхокардиография; bicuspid aortic valve; children; CD25+ interleukin-2 receptor-bearing activated lymphocytes; CD95+ subpopulation of lymphocytes; dopplerechocardiography